Alokasi waktu pekerja wanita pada industri garmen di daerah Sanur kecamatan Denpasar selatan=Time Allocation of Female Workers in the Garment Industry in.the Village of Sanur, South Denpasar - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT The aims of this study in general are to know the time allocation of the respondents' job in the public sector and several factors which affect it. The role of women in the household economy can be clearly observed from the contribution of female workers to the household income. Besides, the aims of the study are to know the outlines of the demographic characteristics and the conditions of married female workers who work under the putting out system in the garment industries. The objectives of the study are also to get some clear illustration on the utility of female workers looked upon from both their working hours as well as the income they receive. The result of the regression analysis shows that there were three factors which influence significantly on the working hours of the respondents in the public sector: the age of the youngest child, the average income per hour, and culture. The strongest was the cultural factor which brought some negative influence on the wokring hours of the respondents. The second strongest influence was the age of the youngest child, whereas the avereage wage per hour had the weakest influence. The two last mentioned factors had a positive effect on the working hours in the public sector. From the view point of working hours, more than 90 percent of respondents were fully employed. However, concerning the wages they received, more than 90 percent claimed that their total income was far bellow their basic household ',Perk Hence, the majority of respondents claimed that their income were not much utilized. The two phenomena mentioned above reflected the female workers in the garment industries, particularly those who worked at home with relatively low productivity.